“La identidad cultural en el proceso de enseñanza-aprendizaje en los niños del quinto año de educación básica paralelo “A” de la unidad educativa Pastocalle, perteneciente a la provincia de Cotopaxi cantón Latacunga, parroquia Pastocalle año lectivo 2022-2023” - Sanchez Iza, Deysi Yadira (2023)
Cultural identity is a way of life in which values, beliefs and traditions of society are enclosed, in which over time barriers have been created that prevent the identity of belonging of each individual from emerging, essentially within the educational scenario, that is to say, within the school context, where a gap in cultural identity is most evident. For this reason, the present research was carried out with the objective of investigating cultural identity and its incidence within the educational unit under study, due to the social realities of the students who belong to different ethnic social groups. Therefore, it was also essential to know if teachers are able to integrate students in a harmonious educational environment, always respecting the different cultural identities that exist within the educational community. In this way, discrimination between students, teachers to students or students to teachers is eliminated. Therefore, it is important to know what didactic methodologies teachers apply to integrate students within an educational environment. Therefore, a thorough investigation was carried out in the Educational Unit "Pastocalle", in the school year 2022 -2023, where surveys were conducted with students, teachers, and parents of the institution. Using instruments with questions according to the information that has been investigated, within the framework of cultural identity, following the data analysis of the information collected within the institution, to reach the reflection with its respective proposal, seeking to generate a didactic, attractive and innovative methodology that can be used by teachers to promote coexistence and integration of all children in school, respecting the different positions and opinions of each of the educational actors of the institution.